A Comparative Study on the Tropical Atlantic and Pacific Oceans Influence on Precipitation over West Africa - Moneh Conteh; Liu Peng (E3S Web of Conferences)
Precipitation variability significantly influences socio-economic activities in West Africa, particularly in sectors such as agriculture, water resources, and food security. This study investigates the influences of the tropical Atlantic Ocean's Atlantic Zone 3 (Atl3 index) and the tropical Pacific Ocean's EI Nino-Southern Oscillation (ENSO) on precipitation patterns across WA. Utilizing high-resolution monthly datasets from 1981 to 2023 we perform composite analyses to evaluate precipitation anomalies and associated atmospheric circulations during key climate modes. Results reveal that EI Nino and the Negative Atl3 events are associated with suppressed precipitation and enhanced subsidence over the region, while La Nina and the Positive Atl3 events drive increased precipitation, especially along the Guinean coast. These findings underscore the need for integrated climate monitoring systems to enhance precipitation forecasting and inform adaptive water resource management strategies.